Basal Forebrain Impairment: Understanding the Mnemonic Function of the Septal Region Translates in Therapeutic Advances - Tsanov, Marian (Frontiers in Neural Circuits, 2022)
The basal forebrain is one of the three major brain circuits involved in episodic memory formation together with the hippocampus and the diencephalon. The dysfunction of each of these regions is known to cause anterograde amnesia. While the hippocampal pyramidal neurons are known to encode episodic information and the diencephalic structures are known to provide idiothetic information, the contribution of the basal forebrain to memory formation has been exclusively associated with septo-hippocampal cholinergic signalling. Research data from the last decade broadened our understanding about the role of septal region in memory formation. Animal studies revealed that septal neurons process locomotor, rewarding and attentional stimuli. The integration of these signals results in a systems model for the mnemonic function of the medial septum that could guide new therapeutic strategies for basal forebrain impairment (BFI). BFI includes the disorders characterised with basal forebrain amnesia and neurodegenerative disorders that affect the basal forebrain. Here, we demonstrate how the updated model of septal mnemonic function can lead to innovative translational treatment approaches that include pharmacological, instrumental and behavioural techniques.